A case for a functional linguistic knowledge base in world language teacher education. (21st August 2019) - Troyan, Francis J.; Sembiante, Sabrina F.; King, Nicole
Abstract: This article contributes to broader discussions of the knowledge base for language teacher education; the standards and policies that inform world language teacher education; and the need for a systematic, principled, and robust theory of language to underpin contexualized world language teaching and learning. Specifically, it proposes that the foundation for world language teacher education be broadened and that the linguistics component of the ACTFL/CAEP Program Standards for the Preparation of Foreign Language Teachers be more clearly defined. The argument is supported using data from a longitudinal ethnographic case study that depicts a candidate's appropriation of systemic functional linguistics (SFL) first as a world language teacher candidate and then as a novice teacher in his first year of teaching. Findings depict the candidate's learning and flexible use of SFL and the associated genre pedagogy to contextualize language use for his students across multiple levels of instruction. Given its alignment with contemporary goals as stated in the World‐Readiness Standards for Learning Languages, instructional approaches, and assessment paradigms, SFL seems to hold great potential as a contextualized and unifying theoretical foundation for world language teacher education. The Challenge: The profession's expectations for what aspiring world language teachers need to know and be able to do represent a continually evolving and sometimes controversial topic. How has the knowledge base been defined? To what extent does systemic functional linguistics offer a contextualized and unifying theoretical foundation for world language education?